Juridical Analysis of Money Laundering Crimes in Financial Technology Based Equity Crowdfunding Services in Indonesia - Adil Putra Halawa (CERED Indonesia Institute, 2022)
The importance of the convenience of practical and efficient financial transactions in today's business world, has led to new innovations in the financial sector called financial technology or (fintech). The type of research carried out is normative juridical research by proposing legislation in conducting the study, selecting the type of normative juridical research, then this research is also supported by empirical data in which the researcher conducts interviews with the Head of OJK Regional 5 North Sumatra Office, and the Prosecutor. The scope and rules regarding fintech services based on equity crowdfunding in Indonesia are first registration, Second Regulatory Sandbox, Third Operator Licensing and Approval, Fourth Monitoring and Supervision. Legal certainty in regulating money laundering crimes in fintech services based on equity crowdfunding in Indonesia is related to the existence of POJK Number 37/POJK.04/2018 concerning Crowdfunding Services through Information Technology-Based Stock Offerings that have an effect on filling legal gaps in the process of establishing an equity company. crowdfunding and the practice of equity crowdfunding in Indonesia so that legal certainty refers to the implementation of the POJK No. 37/POJK.04/2018 law is clear, plus the existence of Law No. 8 of 2010 strengthens the duties, functions, and PPATK in prevention and eradication Money Laundering crime. The obstacles in preventing the eradication of money laundering crimes in fintech-based equity crowdfunding services in Indonesia are the first obstacles in terms of legal structure, second obstacles in terms of legal substance, and third obstacles in terms of legal culture.